2003
DOI: 10.1046/j.1365-2958.2003.03633.x
|View full text |Cite
|
Sign up to set email alerts
|

GadE (YhiE) activates glutamate decarboxylase‐dependent acid resistance in Escherichia coli K‐12

Abstract: SummaryCommensal and pathogenic strains of Escherichia coli possess three inducible acid resistance systems that collaboratively protect cells against acid stress to pH 2 or below. The most effective system requires glutamate in the acid challenge media and relies on two glutamate decarboxylases (GadA and B) combined with a putative glutamate: g g g g -aminobutyric acid antiporter (GadC). A complex network of regulators mediates induction of this system in response to various media, pH and growth phase signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
188
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 26 publications
(55 reference statements)
7
188
2
Order By: Relevance
“…2C lane 6), indicating that their expression was GadE dependent. We have also confirmed by DNase I footprinting analysis that GadE directly bound to the GAD boxes 19,20) in the promoter regions of these genes (Figs. 5 and 6).…”
Section: Evgs/evga Up-regulated Genes Targeted By Evga Ydeo and Gadesupporting
confidence: 72%
“…2C lane 6), indicating that their expression was GadE dependent. We have also confirmed by DNase I footprinting analysis that GadE directly bound to the GAD boxes 19,20) in the promoter regions of these genes (Figs. 5 and 6).…”
Section: Evgs/evga Up-regulated Genes Targeted By Evga Ydeo and Gadesupporting
confidence: 72%
“…Indole-induced expression of mdtEF requires the gadX gene, which encodes an AraC-type transcription factor. GadX is known to induce various genes including gadA, hdeAB and yhiE under low pH conditions (Masuda and Church, 2003;Ma et al, 2003). However, as indole obviously does not cause acidification of the medium, our results indicate that GadX responds to indole even under non-acidic conditions.…”
Section: Discussionmentioning
confidence: 59%
“…Acid resistance is correlated with the ability of both regulators to activate the expression of the gadA and gadBC operons during the stationary phase of growth. The activation of gadA/B expression by GadE requires a GadE-binding box upstream of the promoter Ma et al, 2003). Deletion and mutation analyses of gadA/BC regulatory regions did not reveal a motif that would specifically affect RcsB-dependent activation without affecting that of GadE.…”
Section: Discussionmentioning
confidence: 86%
“…3(a). The gadA, gadB, gadX and gadE fusions were described by and Ma et al (2002Ma et al ( , 2003; the limits for gadA and gadB are shown in Fig. 3(a).…”
Section: Methodsmentioning
confidence: 99%